HANDASAH AL-LUGHAH AL-'ARABIYAH : MUTHALLAB QAUMY WA HADAF ISTIRATIJI - Ahmed, Nafiza Nibal Muallem (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
Given the importance of teaching techniques in the teaching and educational process in modern technology, the adoption of teaching methods was one of the most important inputs of the educational process on whose principles the educational institutions sought to build their educational system. To apply these principles in the different educational stages, Arabic Language Engineering emerged at the forefront of other technologies due to the educational outputs obtained from learners, especially Arabic non-native speakers, and educational institutions. It could thus be a broad aspect to be learnt through this automated program, e.g., Arabic language machines and skills, characteristics and repertoire.